ANATOMO-PHYSIOLOGICAL CHARACTERISTICS OF URINE PRODUCTION AND URINARY SYSTEM IN CHILDREN (Conferencea, 2022)
This thesis gives information about urine production of children. In infants and toddlers, the kidney is round in shape and has a lobed structure, so its surface is rough - this is a sign that the cortical part is not sufficiently developed at this age.